The Meaning of the Earth and the Will of Men: Re-examining the Nietzschean in Wallace Stevens' "Harmonium" - Taylor, Gaye Elizabeth (University of Ottawa (Canada), 2010)
This dissertation is concerned with re-examining "the Nietzschean" in Wallace Stevens' first book of poems, Harmonium (1923). In the final decades of the twentieth-century, such critics as Harold Bloom, J. Hillis Miller, Joseph Riddell, Milton Bates, and B. J. Leggett discovered deep and abiding affinities between Nietzsche's thought and Stevens' poetry. While never denying the existence of a Nietzschean creative will in Stevens, my dissertation argues for significant zones of ambivalence towards Nietzsche's thought in Stevens' poetry, particularly towards the Nietzschean valuation of ''the meaning of the earth." Significantly guided by B. 1. Leggett's readings of Nietzschean intertexts in a number of Stevens' early poems, the second and third chapters of this dissertation seek to supplement---and to complicate---the idea of a Nietzschean will to creative power in Stevens by marking the ways in which these poems extend Nietzsche's mandate by assigning creative agency first to women, and then to "the common man." The last two chapters of the dissertation, however, strike a more independent course, arguing that a number of famous early poems, such as "Sunday Morning" and "The Snow Man," but especially the long poem, "The Comedian as the Letter C," demonstrate that working against an investment in a Nietzschean will to creative power was Stevens' adamant conviction that the limiting function of the earth itself in all its guttural materiality ensured that the outcome of the will to imagine could only ever be, at best, "sufficient"---never self-surpassing.
Keywords: Literature, American.